Odorant‐Binding Proteins and Xenobiotic Metabolizing Enzymes: Implications in Olfactory Perireceptor Events. Issue 9 (31st July 2013) - Heydel, Jean‐Marie; Coelho, Alexandra; Thiebaud, Nicolas; Legendre, Arièle; Bon, Anne‐Marie Le; Faure, Philippe; Neiers, Fabrice; Artur, Yves; Golebiowski, Jérôme; Briand, Loïc; López‐Mascaraque, Laura; Trejo, José Luis
ABSTRACT At the periphery of the olfactory system, the binding of odorants on olfactory receptors (ORs) is usually thought to be the first level of the perception of smell. However, at this stage, there is evidence that other molecular mechanisms also interfere with this chemoreception by ORs. These perireceptor events are mainly supported by two groups of proteins present in the olfactory nasal mucus or in the nasal epithelium. Odorant‐binding proteins (OBPs), the first group of proteins have been investigated for many years. OBPs are small carrier proteins capable of binding odorants with affinities in the micromolar range. Although there is no absolute evidence to support their functional roles in vertebrates, OBPs are good candidates for the transport of inhaled odorants towards the ORs via the nasal mucus. The second group of proteins involves xenobiotic metabolizing enzymes, which are strongly expressed in the olfactory epithelium and supposed to be involved in odorant transformation, degradation, and/or olfactory signal termination. Following an overview of these proteins, this review explores their roles, which are still a matter of debate. Anat Rec, 296:1333‐1345, 2013. © 2013 Wiley Periodicals, Inc.